Pengembangan Media Pembelajaran Berbasis Android Pada Materi Kesetimbangan Kimia - Ramlan Silaban; Melhyada Veronika Panggabean (Universitas Negeri Medan, 2022)
This study aims to determine the feasibility of Android-based chemistry learning media developed based on BSNP standards and to determine student responses to ChemsDroid media. The model used in this research is a 4-D development method from 3 stages, namely: (1) define; (2) design; and (3) development. ChemsDroid android-based media development received an assessment from 3 expert lecturers (material experts and media experts), two chemistry teachers and research samples. The research population was all students of class XII MIA SMA Negeri 1 Perbaungan. The research sample was 1 class XII MIA using total sampling technique. The instrument used was a media feasibility questionnaire non-test instrument based on BSNP standards. Based on the results of data analysis, the Android-based chemistry learning media developed have met the eligibility standards of the BSNP with an average feasibility of 3.61 with very valid criteria and do not need to be revised. The results of student responses to ChemsDroid media obtained a total percentage of 97.71%, which means that students receive and respond to the media very well.